Serum miR-96-5P and miR-339-5P Are Potential Biomarkers for Multiple System Atrophy and Parkinson's Disease - Vallelunga, Annamaria; Iannitti, Tommaso; Capece, Sabrina; Somma, Gerardina; Russillo, Maria Claudia; Foubert-Samier, Alexandra; Laurens, Brice; Sibon, Igor; Meissner, Wassilios G.; Barone, Paolo; Pellecchia, Maria Teresa (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) and Multiple System Atrophy (MSA) are progressive neurodegenerative diseases with overlap of symptoms in early stages of disease. No reliable biomarker exists and the diagnosis is mainly based on clinical features. Several studies suggest that miRNAs are involved in PD and MSA pathogenesis. Our goal was to study two serum circulating microRNAs (miR-96-5p and miR-339-5p) as novel biomarkers for the differential diagnosis between PD and MSA. Serum samples were obtained from 51 PD patients, 52 MSA patients and 56 healthy controls (HC). We measured levels of miRNAs using quantitative PCR and compared the levels of miR-96-5p and miR-339-5p among PD, MSA and HC groups using ANOVA test. Correlations between miRNA expression and clinical data were calculated using Pearson’s rho test. We used the miRTarBase to detect miRNA targets and STRING to evaluate co-expression relationship among target genes. MiR-96-5p was significantly increased in MSA patients compared with HC (Fold change (fc): 3.6; p=0.0001) while in PD compared with HC(Fold change: 4; p=0.0002) was decreased. Higher miR-96-5P levels were directly related to longer disease duration in MSA. We observed a significant increase of miR-339-5p in MSA patients as compared with PD (fc: 2.5; p=0,00013). MiR-339-5p was increased in MSA patients compared with HC (fc: 2.4; p=0.002). We identified 32 target genes of miR-96-5p and miR-339-5p, some of which are involved in neurodegenerative diseases such as BDNF and GDNF. The study of those miRNAs could be useful to identify no invasive biomarkers to early differential diagnosis between PD and MSA.